2019
DOI: 10.1051/epjap/2019190131
|View full text |Cite
|
Sign up to set email alerts
|

A study of multilayer nanostructures [(Co45Fe45Zr10)35(Al2O3)65/a-Si:H]100 and [(Co45Fe45Zr10)35(Al2O3)65/a-Si]120 by means of XRD, XRR, IR spectroscopy, and USXES

Abstract: Interatomic interactions and superstructures of multilayer nanostructures (MLNS) consisting of ferromagnetic composite layers and silicon interlayers with or without hydrogen are studied here by means of X-ray diffraction (XRD), X-ray reflectivity (XRR), IR spectroscopy, and ultra-soft X-ray emission spectroscopy (USXES). The MLNS [(Co45Fe45Zr10)35(Al2O3)65/a-Si:H]100 and [(Co45Fe45Zr10)35(Al2O3)65/a-Si]120 were deposited on the substrate Si(100) by ion-beam sputtering of two targets, where the first target wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Therefore, the study of the composition and morphology of multilayer nanostructures is very relevant for spintronic applications. Our previous work showed a decrease in periods of superstructure relative to the nominal values due to the interfacial interactions on the surface and interfaces of MLs with metal‐containing composite layers (Co 45 Fe 45 Zr 10 ) 35 (Al 2 O 3 ) 65 6,7 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the study of the composition and morphology of multilayer nanostructures is very relevant for spintronic applications. Our previous work showed a decrease in periods of superstructure relative to the nominal values due to the interfacial interactions on the surface and interfaces of MLs with metal‐containing composite layers (Co 45 Fe 45 Zr 10 ) 35 (Al 2 O 3 ) 65 6,7 …”
Section: Introductionmentioning
confidence: 98%
“…Our previous work showed a decrease in periods of superstructure relative to the nominal values due to the interfacial interactions on the surface and interfaces of MLs with metal-containing composite layers (Co 45 Fe 45 Zr 10 ) 35 (Al 2 O 3 ) 65 . 6,7 In this paper, we investigate the morphology of multilayer value significantly affects the magnetic properties. 8 For example, it was found that multilayer CoFeB-SiO 2 /C structures with a cluster structure of CoFeB layers have long-range magnetic order in the entire temperature range from 2 to 300 K. 9 The composition of the magnetic alloy in metal-containing composite layers of MLs is made below the percolation threshold.…”
Section: Introductionmentioning
confidence: 99%